Vagrants’ Communication Behavior in Interpersonal Relations in Jakarta - Syaiful Rohim (Buletin Al-Turas, 2020)
Abstract The study aimed to know the communication management pattern of interpersonal communicationactivities among vagrants and other communities. The study made use of qualitative researchintended to get complete description of interpersonal communication phenomena that occurredamong vagrants and other communities. The research relied on observation and in-depth interviewswith ten vagrants which were spread in some places in Jakarta, Depok, Tangerang Selatan,Tangerang, Bogor, and Bekasi.  The collected data were analyzed using Johari Window theory toexplain which frame underlay how vagrants conducted interpersonal and intrapersonalcommunication. The result showed that vagrants did their communication activities by dividingthemselves into open and close areas. The other communication behavior was done throughmechanism management of impression which was made to manage and organize how to behave ininterpersonal communication and relation with others as a form of adaptation and an effort to keepharmony in social interaction and communication. It can be concluded that the vagrants are part ofthe social system and structure of the community that has traditions and culture that need to berespected and appreciated. Keywords: vagrant; self; impression management, Johari Window